Roberto Melaragno's scientific contributions to Brazilian Neurology - João Carlos Papaterra Limongi; Plinio Marcos Garcia Lima; Sonia Maria César de Azevedo Silva; Matheus Gomes Ferreira; Egberto Reis Barbosa; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Roberto Melaragno Filho, an associate professor of neurology at the School of Medicine of Universidade de São Paulo and head of the neurology service at Hospital do Servidor Público Estadual Francisco Morato Oliveira (HSPE-FMO), had a significant scientific career. He is recognized as a reference in the 20th century Brazilian neurology in addition to having a notable international career.